Lateral load behaviour of GFRG infilled RC frame with CFS connection - local and global behaviour - Shaji, Aishwarya; Prasad, A. Meher; Menon, Devdas (Journal of Structural Engineering, 2024)
Glass Fibre Reinforced Gypsum (GFRG) panels can be used as infills in multi-storeyed framed construction, and the lateral load behaviour of GFRG infilled Reinforced Concrete (RC) frames is strongly influenced by the filling inside the cavities of the panel. When the cavities of the panel are left unfilled, the connection between the GFRG panel and the RC frame is established using Cold-Formed Steel (CFS) sections with suitable screw connections. A quasi-static cyclic lateral load test was performed on GFRG infilled RC frame with empty cavities to understand their behaviour. The results highlighted the significance of the screw connection between the GFRG panel and CFS plate, which experiences shear, in determining the behaviour of GFRG infilled RC frames. Therefore, the behaviour and strength of the screw connection between CFS profiles and the GFRG panel was studied by conducting monotonic and cyclic shear load tests. The results demonstrated the influence of CFS plate thickness, screw diameter, edge distance of the screws and placement of the CFS plate on various performance parameters of CFS-GFRG screw connection.